Implementation of al-Ma’un Theology: The Movement of Muhammadiyah Educated Groups in Poverty Alleviation in Bulutellue Village, Sinjai Regency - Abdul Rahman; Muhammad Syukur; Jumadi Jumadi (State Institute of Islamic Studies (IAIN) Salatiga, 2021)
In the concept of Islamic community development, welfare is an ideal condition for any social life. Efforts to create prosperity in Bulutellue Village also received attention from the Muhammadiyah education group. They invite the community, especially those from the rich to provide sustainable assistance to groups of the poor and orphans as a form of mainstreaming al-Ma’un theology. This study aims to describe the implementation of al-Ma’un theology in alleviating poverty in Bulutellue Village, Sinjai Regency. This study employed a qualitative method. The data were collected through observation and interviews. The results indicate that al-Ma’un theology was introduced by the educated group of Muhammadiyah Higher Education to the community of Bulutellue Village. This doctrine is accepted and implemented by the community in this village even though they are not registered as official members of the Muhammadiyah organization as an effort to make their income a way of gaining happiness and getting blessings from Allah SWT towards mutual benefit.